tg (x-y) = (tgx-tgy)/(1+tgx*tgy)
![tg(\frac{\pi }{4} -a) = \frac{tg(\pi/4)-tga }{1+tg(\pi/4)*tga } = \frac{1-tga}{1+tga} tg(\frac{\pi }{4} -a) = \frac{tg(\pi/4)-tga }{1+tg(\pi/4)*tga } = \frac{1-tga}{1+tga}](https://tex.z-dn.net/?f=tg%28%5Cfrac%7B%5Cpi%20%7D%7B4%7D%20-a%29%20%3D%20%5Cfrac%7Btg%28%5Cpi%2F4%29-tga%20%7D%7B1%2Btg%28%5Cpi%2F4%29%2Atga%20%7D%20%3D%20%5Cfrac%7B1-tga%7D%7B1%2Btga%7D)
для того, чтобы найти тангенс, нужен косинус. На заданном промежутке он будет отрицательный.
cos²a = 1-sin²a = 1-(2/4) = 1-(1/2) = 1/2
cosa = -√2/2
тангенс = синус/косинус = √2/2 * (-2)/√2 = -1
tg (π/4 - a) = (1-(-1))/(1-1) = 2/0 - не существует.